2013
DOI: 10.1016/j.jneuroim.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in circulating levels of neutrophil extracellular traps in serum of multiple sclerosis patients

Abstract: Neutrophil extracellular traps (NETs) trap and kill pathogens very efficiently but also activate dendritic cells and prime T cells. Previously, we demonstrated that neutrophils are primed and circulating NETs are elevated in relapsing remitting multiple sclerosis (RRMS), a T cell-mediated autoimmune disease. Here, we demonstrate gender specific differences in circulating NETs but not in neutrophil priming in RRMS patients. Although the results from our systematic and in depth characterization of these patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 48 publications
2
56
1
Order By: Relevance
“…Interestingly, there was a significant difference in the levels of hc-DNA between male and female healthy volunteers, which is in contrast to the results of Tillack et al [23]. In their work, Tillack et al detected gender differences in patients diagnosed with remittent-relapsing multiple sclerosis, but not in healthy volunteers or any other patient group under investigation.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, there was a significant difference in the levels of hc-DNA between male and female healthy volunteers, which is in contrast to the results of Tillack et al [23]. In their work, Tillack et al detected gender differences in patients diagnosed with remittent-relapsing multiple sclerosis, but not in healthy volunteers or any other patient group under investigation.…”
Section: Discussioncontrasting
confidence: 57%
“…NETs are extracellular matrices composed of fibers containing DNA, decondensed chromatin, histones, and antimicrobial proteins that immobilize and kill microbes [33, 34]. Although beneficial during infection, NETs have been associated with pathophysiological conditions, including MS. A subset of RRMS patients have higher circulating levels of NETs in their sera, although higher levels of NETs did not correlate with disease activity [18, 35]. Interestingly, in vitro studies demonstrated that transendothelial migration of neutrophils across brain endothelium triggered the release of NETs that contributed to neuronal cell death [36].…”
Section: Neutrophil Functionmentioning
confidence: 99%
“…In mice, G-CSF is important for the mobilization and maturation of neutrophils (27), and neutrophil recruitment to the CNS is critical for EAE development (3-5) through proposed effector mechanisms such as the disruption of the blood-brain barrier and the maturation of antigen-presenting cells (3). In parallel, neutrophils in patients with MS are found to be more numerous and in a primed state (28) with elevated levels of the CD11b integrin (29), and greater propensity to form neutrophil extracellular traps particularly in male compared with female patients with MS (30). In addition, levels of systemic neutrophil chemokines correlate with indices of brain lesion formation in MS (5), and neutrophils have been observed in areas of blood-brain barrier disruption in early lesions of MS (31).…”
Section: Gestational Bpa Exposure Alters Responses Of Macrophages Culmentioning
confidence: 99%